Indian Tribal Religious System of the Santal Society of Northern Odisha: A Historical Analysis - Mohapatra, Ratnakar; Hembram, Singo (International Journal of Psychosocial Rehabilitation, 2025)
India has been truly considered as a country of various races and tribes in South-East Asia. Tribals are differently known as Jantjati, Adimjati, Anusuchit Janjati and Adivasi. Odisha occupies a special position in the tribal map of India. There are as many as seven hundred and five tribes noticed in different parts of India, but in Odisha the number is sixty-two. In fact, the Santals are leading in the tribal communities of Odisha in Eastern India. The Santals are mostly resided in the Mayurbhanj, Keonjhar and Balasore districts of Odisha in Eastern India. The religion of Santals consisted of prayers, sacrifices and religious dances. The Santals are highly ritualistic people and regard their sprit as their Lords and protectors. The Santals have indistinguishable concept regarding the supernatural being i.e. bonga. The ancestral worship of the Santals occupies an important place in their religious beliefs. For the Santals, the rituals and ceremonies evoke an emotion that goes beyond a mere response to the practical needs. The Santal people bind the community together in their belief and give them a sense of the sacredness. There is no temple for the worship of gods and goddesses of the Santals of Northern Odisha. The sacred places of the Santals of are Jaherthan , Majhi than, etc. The Santals hold a strong religious faith and their religion is considered as “animism” or “Bongaism”. The traditional religious customs of the Santals of Mayurbhanj, Keonjhar and Balasore are mostly prevalent in their society till today. In some extent, the psychology of the people of Santal tribe / community is slightly changed due to the impact of modern education, industrialization and Hinduism. The Santals have a number of festivals throughout the year. Some festivals are connected with agricultural operation; some festivals are associated with their religions and a few festivals are observed by them for hunting purpose. The present article aims to focus on the prevalent religious belief, practices, rituals and festivals observed by the Santals of Northern Odisha in East India. For the writing of this article, both the primary and secondary sources are meticulously used by the author.